The method for design of electromagnetic hybrid active-passive shielding by overhead power lines magnetic field - Kuznetsov, B. I.; Nikitina, Nikitina; Bovdui, I. V.; Chunikhin, K. V.; Kolomiets, V. V.; Kobylianskyi, B. B. (Національний технічний університет "Харківський політехнічний інститут", 2024)
Development of the method for designing electromagnetic hybrid active-passive shield, consisting from active and multy-circuit passive parts, which is characterized by increased effectiveness of reducing the industrial frequency magnetic field created by twocircuit overhead power lines in residential buildings. Methodology. The designing problem of electromagnetic hybrid active-passive shield including robust system of active shielding and multy circuit passive shield of initial magnetic field comes down to a solution of the multy-criteria two-player zero-sum antagonistic game. The game payoff vector calculated based on the finite element calculations system COMSOL Muliphysics. The game solution calculated based on the particles multyswarm optimization algorithms. Results. During the design of the electromagnetic hybrid active-passive shield the coordinates of the spatial arrangement of 11 circuits passive shield and the coordinates of the spatial location of one compensation winding, as well as the current and phase in this winding of the active shielding system are calculated. The results of theoretical and experimental studies of hybrid active and multy-circuit passive shield by magnetic field in residential building from two-circuit power transmission line with a «Barrel» type arrangement of wires presented. Originality. For the first time the method for designing hybrid active and multycircuit passive shield, consisting from active and multy-circuit passive parts, which is characterized by increased effectiveness of reducing the magnetic field of industrial frequency created by two-circuit overhead power lines in residential buildings is developed. Practical value. Based on results of calculated study the shielding efficiency of the initial magnetic field what is confirmed by experimental studies determined that shielding factors whith only multy-circuit passive shield is more 1.2 units, whith only active shield is more 4 units and with electromagnetic hybrid active-passive shield is more 6.2 units. It is shown the possibility to reduce the level of magnetic field induction in residential building from two-circuit power transmission line with a «Barrel» type arrangement of wires by means of electromagnetic hybrid active shielding with single compensating winding and multy-circuit passive shielding with 11 circuit passive shield to 0.5 μT level safe for the population.

Розробка методу проектування електромагнітного гібридного активно-пасивного екрану, який складається з активної та багатоконтурної пасивної частин, та характеризується підвищеною ефективністю зниження магнітного поля промислової частоти, що генерується дволанцюговими повітряними лініями електропередачі в житлових будинках. Методологія. Задача проектування електромагнітного гібридного активно-пасивного екрану, яка включає розробку робастної системи активного екранування та багатоконтурного пасивного екрану вихідного магнітного поля, зводиться до вирішення багатокритеріальної антагоністичної гри двох гравців з нульовою сумою. Вектор виграшів гри розраховується з використанням кінцево-елементної системи обчислень COMSOL Muliphysics. Рішення гри розраховується на основі алгоритмів оптимізації мультироїв частинок. Результати. При проектуванні електромагнітного гібридного активно-пасивного екрану були розраховані координати просторового розташування 11 контурів пасивного екрану і координати просторового розташування однієї компенсаційної обмотки, а також струм і фаза в цій обмотці системи активного екранування. Наведено результати теоретичних та експериментальних досліджень електромагнітного гібридного активно-пасивного екрану магнітного поля в житловому будинку від дволанцюгової лінії електропередач із розташуванням проводів типу «бочка». Оригінальність. Вперше розроблено метод проектування електромагнітного гібридного активно-пасивного екрану, який складається з активної та багатоконтурної пасивної частин, та характеризується підвищеною ефективністю зниження рівня магнітного поля промислової частоти, яке генерується дволанцюговими повітряними лініями електропередачі в житлових будинках. Практична цінність. За результатами розрахункових досліджень ефективності екранування вихідного магнітного поля, які підтверджені експериментальними дослідженнями, встановлено, що коефіцієнт екранування тільки багатоконтурним пасивним екраном становить більше 1,2 одиниць, а тільки з активним екраном становить більше 4 одиниць, і при використанні електромагнітного гібридного активно-пасивного екрану становить більше 6,2 одиниці. Показана можливість зниження рівня індукції магнітного поля в житловому будинку від дволанцюгової лінії електропередачі з розташуванням проводів типу «бочка» за допомогою гібридного активного екрану з однією компенсуючою обмоткою та багатоконтурного пасивного екрану з 11 контурами до безпечного для населення рівня в 0,5 μT.
Keywords: overhead power line; magnetic field; electromagnetic hybrid active-passive shield; computer simulation; experimental research; повітряна лінія електропередачі; магнітне поле; електромагнітний гібридний активно-пасивний екран; комп'ютерне моделювання; експериментальні дослідження